Faktor Hambatan dan Upaya Pemerintah Desa terhadap Pengelolaan Aset Desa Pone Kecamatan Limboto Barat - Annisa Nur Fitriyani Daud; Weny Almoravid Dungga; Julius T. Mandjo (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
This research aims to determine the role of the village government in managing the assets of Pone Village, West Limboto District and to determine the factors that hinder the village government in managing the assets of Pone Village, West Limboto District. The type of research used by prospective researchers is Empirical Legal research with a qualitative approach. Empirical legal studies themselves are studies that view law as reality, including social realities, cultural realities, and empirical studies of the world of das sin (what is the reality). The results of the research show that the role of the Pone Village government in managing village assets is not optimal because in the series of planning and utilization processes , maintenance, administration and reporting carried out by the Pone village government are not yet based on applicable regulatory provisions. There are several inhibiting factors in managing village assets such as village-owned assets that do not have legal certainty in the form of proof of ownership in the name of the village government, weak human resources in managing owned assets villages, and budget financial constraints in supporting the management of village assets.